The election of the evangelical Jimmy Carter, Gerald Ford, and the presidential contest of 1976 - Williams, Daniel K. (American presidential elections., 2020)
"From the perspective of the early twenty-first century, the 1976 election looks like an odd anomaly: a bygone moment when the evangelical candidate with strong support from his fellow Southern Baptists was a Democrat and the Republican candidate was a social moderate whose wife loudly proclaimed her support for Roe v. Wade and who was able to win culturally liberal states such as Oregon, California, and New Jersey, even while losing Ohio, Texas, and nearly the entire South. But the 1976 election was a pivotal turning point: a harbinger of a new culturally polarized politics that differentiated the parties according to values-based ideologies. Even though both nominees were centrists, both parties were pulled further to the extremes during the election year, setting up the divides of the 1980s and beyond. The story immediately following 1976 was that a self-described "evangelical Christian" and improbable dark-horse candidate from the Deep South won the presidency, which led Newsweek magazine to call 1976 the "year of the evangelical." But what people missed at the time was the effect that this election had on the parties. The Election of the Evangelical traces this watershed moment by doing what no other study of the 1976 election has done: it explains how and why the primary campaigns and the events leading up to the general election reshaped both the Democratic and Republican parties along lines that reflected the nation's cultural divisions"--